Kesenjangan Komunikasi Digital Mahasiswa Perguruan Tinggi Keagamaan Dengan Perguruan Tinggi Umum di Indonesia - Dyatmika, Teddy; Farhatussho Imah, Farah; Febriyanti, Ayu; Gunawan, Feri (IAI Darussalam, 2024)
The ranking of the Ministry of Religion Universities is far behind compared to the Ministry of Education and Culture Universities according to webometrics and Unirank. This is an indicator of the digital divide. With equal Internet access, there should be no digital divide. The purpose of this study was to determine the digital divide between students from the Ministry of Religion Universities and students from the Ministry of Education and Culture Universities. The theory used in this study is the theory of digital divide which includes three aspects, namely access divide, usage divide, and quality of use divide. The population in this study was 8,825,981 students with a sample of 424 respondents. The sampling technique used was simple random with a standard error of 4.82%. The data analysis technique used the SPSS compare means one way ANOVA test. The results showed that the access divide and the usage divide did not experience a digital divide with a significance value of 0.80 and 0.909, respectively. Meanwhile, the quality of use divide experienced a digital gap with a significance value of 0.024. The digital divide occurs in the quality of students' use of information and communication technology. The average quality of the use of information and communication technology among university students of the Ministry of Education and Culture is higher than that of university students of the Ministry of Religion. There needs to be an effort from the Ministry of Religion in making policies so that the use of information and communication technology in Higher Education students of the Ministry of Religion is of higher quality, especially in accessing national and international journals.